Implementation of nurse’s clinical competency: A scoping review - Suarmayasa, I Nengah; Swarjana, I Ketut; Adi Satriani, Ni Luh; Noviana Sagitarini, Putu (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2024)
Background: Nursing care provided to patients, especially in hospitals, is expected to be of high quality, and its implementation is in accordance with the nurse's clinical competence. Objectives: This scoping review aimed to assess the implementation of the clinical competence of nurses in hospitals so that a clear picture of the implementation of these competencies is obtained. In addition, this study can be evidence-based and related to implementing these clinical competencies. Methods: This literature review used PICO framework to develop articles questions (P: nurses, I: not applicable, C: not applicable, and O: application of clinical nursing competency). Articles search for literature review was conducted during April and May 2023. This study used Pubmed and ScienceDirect Databases and other sources. The keywords that used in this scoping review was “nursing competency” OR “clinical nursing competency” AND “evaluation” OR “implementation” AND “hospital”.Results: There were 1,150 articles from the search results, but only seven were included for review. One article is a descriptive comparative study using a qualitative approach, and six articles are cross-sectional studies. The articles are publications within five years (2019-2023). In its implementation, the average clinical competency of nurses is at a low to moderate level, and only one study found was at high nurse competency. The results of the supervisor's clinical competency assessment were significantly lower than those assessed by oneself and the group. In addition, the nurse competency level was moderate, and there was no significant difference in the clinical competency of nurses before and during the COVID-19 pandemic.Conclusions: The implementation of nurses' clinical competence has yet to be optimal, so hospital management needs to improve nurses' clinical competence so that nurses can provide higher quality and professional nursing care in the hospital.